The ideal protein profile for late-finishing pigs in precision feeding systems: Threonine - Remus, A. [UNESP]; Hauschild, L. [UNESP]; Létourneau-Montminy, M. P.; Corrent, E.; Pomar, C. [UNESP] (Elsevier, 2020)
Optimal amino acid ratios for pigs have been established for conventional phase feeding systems, but these ratios may differ for precision feeding systems. Our objective was to assess the impact of different dietary Thr inclusion levels (70, 85, 100, 115, or 130% of the estimated ideal 0.65 Thr:Lys ratio) on growth performance, plasma biochemical parameters, and splanchnic and muscle AA composition in pigs raised in a conventional group phase feeding (GPF) system and in an individual precision feeding (IPF) system. A total of 110 finishing pigs (110 ± 7.02 kg initial body weight; 11 pigs per treatment) were housed in the same room for 21 d. Pigs were randomly assigned to a 2 × 5 factorial arrangement and fed using automatic feeders. Individual pigs were considered the experimental units. Five pigs per treatment were slaughtered at the end of the trial. The gain:feed ratio was not affected by feeding system, but there was a quadratic effect of Thr inclusion rate (P < 0.05). Lysine intake was 16% greater and Thr intake was 15% greater for the GPF pigs than for the IPF pigs (P < 0.05). Protein deposition (g/d) was not affected by any treatment. Protein deposition in daily gain was affected by the interaction between Thr inclusion rate and feeding system, with a quadratic (P < 0.05) effect for the GPF pigs and a cubic (P < 0.10) effect for the IPF pigs. The pigs in IPF consumed 14% less (P < 0.05) crude protein and excreted 17% less (P < 0.05) N than the GPF pigs did. The pigs in IPF retained 9% more (P < 0.05) N than the GPF pigs. Plasma urea values were 9% higher (P < 0.05) in GPF than those in IPF. The gamma-glutamyl transferase enzyme decreased (P < 0.05) in a quadratic manner within IPF but increased (P < 0.05) in a quadratic manner within GPF. In the IPF systems, the average concentration of albumin and C-reactive protein tended (P < 0.10) to be 2 and 22% lower, respectively, than in GPF. Changes in amino acid concentrations occurred mainly in the liver of the IPF pigs. The pigs in IPF had higher (P < 0.05) concentrations of collagen in the longissimus dorsi than the pigs in GPF. Lastly, IPF allowed standardized ileal digestible Lys and Thr intakes to decrease by 16 and 15%, respectively, without differences in average daily gain and gain:feed ratio in comparison with GPF.
Keywords: Amino acid concentration; Blood plasma parameters; Body composition; Group phase feeding; Lysine; Splanchnic tissue composition